(untitled) (CIPEEX, 2024)
THE MAIN OBJECTIVE WAS TO COMPILE DATA THAT ALLOW EVALUATING THE INFLUENCE OF TRAINING ON IMPROVING FLEXIBILITY IN HANDBALL GOALKEEPERS. A LONGITUDINAL DESCRIPTIVE CASE STUDY WAS CARRIED OUT, WITH TWO TEENAGE MALE GOALKEEPERS AGED 15 AND 18 YEARS OLD, THERE WERE NO CRITERIA FOR THE SELECTION OF GOALKEEPERS, THEREFORE, IN THE DEVELOPMENT OF THIS WORK, WELL BANK, AND FORMS WERE USED. FOR EVALUATION AND DATA RECORDING. THE PROCEDURES WERE DEVELOPED IN TEN TRAINING SESSIONS SUBDIVIDED TWICE A WEEK, AND CARRIED OUT IN THE MORNING, IN WHICH EACH DAY PASSIVE GLOBAL STRETCHING WAS CARRIED OUT FOR 10 SECONDS UP TO A FEW MINUTES, IN PASSIVE-DYNAMIC STRETCHING EXERCISES THERE IS MOVEMENT OF OSCILLATION WITH VARYING RHYTHM AND AMPLITUDES BEFORE, IN WHICH EACH EXERCISE WAS PERFORMED FOR THIRTY SECONDS, AND IMMEDIATELY AFTER TRAINING WITH THE TEAM, THE GOALKEEPERS BEGAN STRETCHING AGAIN, BUT IN AN ACTIVE WAY. EXERCISES WERE CHOSEN TO WORK THE MAIN MUSCLE GROUPS: PECTORAL, DORSAL, QUADRICEPS, BICEPS FEMORIS, BICEPS BRACHII, TRICEPS AND LUMBAR REGION, THE MOVEMENTS PERFORMED WERE QUADRICEPS EXTENSION, KNEE FLEXION, SHOULDER EXTENSION, HAMSTRING FLEXION, LUMBAR FLEXION, AND TRUNK FLEXION. BY CARRYING OUT THE TEST AFTER 10 TRAINING SESSIONS, AN INCREASE IN FLEXIBILITY OF FIVE CM WAS OBSERVED IN ONE TEENAGER, AND THREE CM IN ANOTHER, HOWEVER THE RESULTS FOR BOTH JUMPED FROM GOOD TO EXCELLENT. CONSIDERING AND COMPARING THE TWO EVALUATIONS, THE STUDY WAS POSITIVE, AS ITS OBJECTIVE WAS TO PROVIDE THESE GOALKEEPERS WITH TRAINING THAT DEVELOPED FLEXIBILITY, AND ANALYZING THE COLLECTIONS, THERE WAS AN INCREASE IN BOTH GOALKEEPERS.